Stability analysis of different winter wheat genotypes in long-term experiment - Szabó, Éva (Acta Agraria Debreceniensis, 2012)
Nowadays, due to the climate change, it is becoming increasingly important in the occasionally extreme years that the yield and the qualityparameters of a given winter wheat variety should not fluctuate at all or only slightly under similar agrotechnical conditions as a result of the year effect. In four years (2005–2008) we studied the changes in the wet gluten content, gluten speading and protein content of five wheat genotypes at six fertilization levels.In the control, it can be observed that the year had a significant effect on the wet gluten content, the protein content of the flour and gluten speading, therefore, a great fluctuation was detected in these qualities of the varieties in the four studied years. At the optimum fertilization levels (N120-150+PK), the varieties Sixtus, Saturus and Lupus showed a much lower fluctuation and more stable values were measured. The most stable variety in the control treatment was Mv Mazurka for all the three quality parameters, while at the optimum fertilization level (N120+PK), the most stable results were obtained for the variety Sixtus as an average of the four years.When studying the results using Kang’s method for stability analysis, it can be stated that the most stable values of wet gluten content were obtained at the fertilization level of N120+PK under a variable year effect, the varieties gave also the best gluten content values at this level. The most stable protein content values of flour were obtained at the fertilization level of N60+PK. The results showed that the fluctuation of quality parameters as a result of the changing years differed between the different winter wheat varieties due to their differing genotypes, but this fluctuation could be reduced or minimized by a proper fertilization.